From disciplinary biopolitics to the psychopolitics of surveillance capitalism - Guillen-Hernández, Eduardo (2024)
The present study concerns the structural mutation traversing the concept of surveillance in contemporary societies and the consequent degradation of the autonomy of the will that this mutation produces, where the disciplinary power that once acted upon the body through confinement and the norm gives way to an extractive psychopolitics that operates upon the psyche through the subcognitive capture of experience, converted into behavioral surplus value susceptible to prediction and sale. It is assumed that this transformation does not constitute a quantitative intensification of the old panoptic paradigm, but a qualitative rupture in the object of power, whereby bodily discipline is replaced by an algorithmic modulation of habits that requires no explicit coercion to produce its effects. It is therefore argued that the architecture of digital choices, articulated through manipulative design patterns and reinforcement learning systems oriented toward maximizing user retention, replaces the rational deliberation demanded by the Kantian doctrine of autonomy with predictive stimuli that anticipate desire before reflection, degrading the self-legislating will into a heteronomous instance that becomes more effective the less perceptible it remains. Likewise, the study examines the extension of this architecture toward electoral microtargeting, where the fragmentation of the electorate into behavioral profiles undermines shared public deliberation. To this end, the study proceeds from a framework that articulates the philosophical critique of biopolitics with technical evidence from behavioral economics and machine learning, understanding behavioral surplus value as the surplus of data that surveillance corporations extract and convert into commercially exploitable predictive products.